Banking across boundaries : placing finance in capitalism - Christophers, Brett, 1971- (Chichester ; Malden, MA : John Wiley & Sons, 2013)
This compelling contribution to contemporary debates about the banking industry offers a unique perspective on its geographical and conceptual 'placement'. It traces the evolving links between the two, revealing how our notions of banking 'productiveness' have evolved alongside the shifting loci of banking activity. An original contribution to the urgent debates taking place on banking sparked by the current economic crisis offers a unique perspective on the geographical and social concept of 'placement' of the banking industry.
The birth of economic productiveness -- Instrumental internationalism -- Enclosing the unproductive -- America, and boundaries breached -- Layering the logics of free trade in banking -- Anaemic geographies of productive finance.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance; Banks and banking; Banks and banking, International; International finance; Capitalism; BUSINESS & ECONOMICS -- Banks & Banking; Banks and banking; Banks and banking, International; Capitalism; Finance; International finance; Electronic books; Electronic books; Electronic books